2006
DOI: 10.1261/rna.2251306
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of an informationally complex high-affinity RNA aptamer to GTP

Abstract: Higher-affinity RNA aptamers to GTP are more informationally complex than lower-affinity aptamers. Analog binding studies have shown that the additional information needed to improve affinity does not specify more interactions with the ligand. In light of those observations, we would like to understand the structural characteristics that enable complex aptamers to bind their ligands with higher affinity. Here we present the solution structure of the 41-nt Class I GTP aptamer (K d = 75 nM) as determined by NMR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 51 publications
4
70
1
Order By: Relevance
“…For example, amino acid binding by riboswitches employs larger RNA structures which can and do bind more tightly than our selected sites, presumably because riboswitch binding must generate free energy required to drive accompanying regulatory reactions. This is as anticipated-larger RNA sites bind GTP better (Carothers et al 2004) because larger sites are better prestructured for nucleotide binding (Carothers et al 2006), rather than because larger sites make more interactions. Though amino acids are somewhat different double-ended ligands with loose linkage, unlike nucleotides, a similar progression might be anticipated, and has been partially characterized for arginine (Geiger et al 1996).…”
Section: Conclusion For Selected Amino Acid Sitessupporting
confidence: 53%
“…For example, amino acid binding by riboswitches employs larger RNA structures which can and do bind more tightly than our selected sites, presumably because riboswitch binding must generate free energy required to drive accompanying regulatory reactions. This is as anticipated-larger RNA sites bind GTP better (Carothers et al 2004) because larger sites are better prestructured for nucleotide binding (Carothers et al 2006), rather than because larger sites make more interactions. Though amino acids are somewhat different double-ended ligands with loose linkage, unlike nucleotides, a similar progression might be anticipated, and has been partially characterized for arginine (Geiger et al 1996).…”
Section: Conclusion For Selected Amino Acid Sitessupporting
confidence: 53%
“…A subset of these in vitro evolved RNAs have been structurally characterized using NMR or crystallographic techniques [55][56][57][58][59][60]. Relevant to riboswitches, the structure of these RNA aptamers bound to AMP, GTP, FMN, and vitamin B12 have been elucidated (Figure 4).…”
Section: Riboswitches Are Sophisticated Versions Of In Vitro Selectedmentioning
confidence: 99%
“…A comparison of the structural basis for ligand binding of AMP, GTP, FMN, and vitamin B12 aptamers demonstrates this point (compare Figure 2a to e and Figure 4). The recently characterized GTP aptamer serves as the closest mimic of the binding mode of riboswitches [57]. All portions of GTP in this structure are recognized and nearly buried.…”
Section: Riboswitches Are Sophisticated Versions Of In Vitro Selectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our graph-based analysis of random pools (25-100 nucleotides [nt]) showed that different RNA secondary topologies are far from uniformly distributed, with low yields for multiply branched structures, although complex structures gradually become more frequent as RNA length increases (Gevertz et al 2005). Interestingly, recent experimental findings suggest that enhancing the structural diversity of RNA pools increases the possibility of obtaining novel RNAs with high activity (Carothers et al 2004(Carothers et al , 2006. Specifically, GTP aptamers with high-binding affinities are found to be more complex structurally than low-binding-affinity aptamers.…”
Section: Introductionmentioning
confidence: 99%